Hybrid Power System Optimization for Cost and Emission Reduction: A Case Study from Indonesia - Muhammad Ridho Rohman Zuhri; Abdullah Umar; Faiz Husnayain (International Journal of Electrical, Energy and Power System Engineering)
Bunaken Island is a remote area that relies on a hybrid power system combining solar photovoltaic (PV) panels and diesel generators to meet its electricity demand. High reliance on diesel increases fuel consumption and carbon dioxide (CO₂) emissions, especially when solar output is low. This research aims to optimize the hybrid system to improve efficiency, reduce fuel consumption, decrease emissions, and minimize energy costs. HOMER software was used to simulate the system by considering load profiles, solar radiation, temperature, and system parameters. Performance indicators included fuel consumption, carbon emissions, and levelized cost of energy (LCOE). The optimized design reduced the LCOE from IDR 2,775/kWh to IDR 2,436/kWh and decreased CO₂ emissions from 511.9 tons/year to 423.5 tons/year. It also reduced diesel consumption from 195,741 liters/year to 161,921 liters/year. These results demonstrate the optimized system’s efficiency and cost-effectiveness in supporting greater integration of renewable energy into Bunaken Island’s electricity generation mix. In addition to these outcomes, the study’s main contribution is a practical optimization model for remote island energy systems that integrates economic, environmental, and technical performance, promoting dedieselization by reducing reliance on diesel fuel. This model provides a replicable framework for other isolated regions facing similar energy challenges, supporting the national transition toward cleaner and more sustainable energy solutions.